ADAB DAN AKHLAK PENUNTUT ILMU YANG DIKISAHKAN DALAM QURAN SURAH AL-KAHFI AYAT 64-70 - Singgih, Muhammad (LPPM STKIP PGRI Bandar Lampung, 2020)
Education is a substantial field for human life because education can encourage the improvement of human quality both in the form of knowledge, attitudes, and skills. It seems that in this day morals are declining due to the lack of serious attention in education. In nowadays, education expects students not only to have cognitive embedded in their self, but also to have noble manners and morals. This research aims to determine the importance of manners and morals of a student towards his teacher. On the other hands, manners and character play a very important role in the blessing of the knowledge gained by students. The method used in this research is the library method with a qualitative approach. From this research, it was found that manners and morals are two important things in the learning process. How a student should focus on his studies, align his intentions and humble himself and be obedient to his teacher is important for students. In the quran surah al-kahfi verses 64-70 have also been told the importance of manners and morals of a student. Indeed, the prominent of manners and morals can be used as a reflection of a student in seeking knowledge.